Implementation of Multiple Linear Regression Methods as Prediction of Village Spending on Village Financial Management System - Nisa Hanum Harani; Hanna Theresia Siregar; Cahyo Prianto (Universitas Trunojoyo Madura, 2019)
The realization of village welfare and improvement of Village development can be started from the financial management aspects of the village. The village government has authority ranging from planning, implementation, reporting to accountability. There are two important variables as the financial aspects, there is village income, and village expenditure. The village budget process is a plan that will be compiled systematically. Planning has an association with predictions which is an indication of what is supposed to happen and predictions relating to what will happen. To provide a good village budget planning the village budget prediction feature is required. This prediction feature is done using data mining which is modeled i.e. multiple linear regression algorithm. The variable is selected using a purposive sampling technique and the sample count is 29 villages. Dependent variables are village Expenditure as Y, and independent variables i.e. village funds as X1 and village funding allocation as X2. The best values as validation were gained in the 3rd fold with a correlation coefficient of 0.8907, Mean Absolute Error value of 87209395.37, the value of Root Mean Squared Error of 114867675.6, Roll Absolute Error (RAE) Percentage was 42 %, and Root Relative Squared Error was 44 %.